2013
DOI: 10.1017/sjp.2013.72
|View full text |Cite
|
Sign up to set email alerts
|

Protective Factors for Adolescent Violence against Authority

Abstract: Both the family and school environments influence adolescents' violence, but there is little research focusing simultaneously on the two contexts. This study analyzed the role of positive family and classroom environments as protective factors for adolescents' violence against authority (parent abuse and teacher abuse) and the relations between antisocial behavior and child-to-parent violence or student-to-teacher violence. The sample comprised 687 Spanish students aged 12-16 years, who responded to the Family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 39 publications
2
30
0
11
Order By: Relevance
“…In previous studies school maladjustment has been associated with child-to-parent violence (Ibabe et al, 2013; Ibabe, 2014), both variables could be indicators of psychological distress in adolescents. Taking into account that we will study a community sample, school failure could be a source of considerable family tension which might interfere with satisfactory relations between adolescents and parents (Hurrelmann et al, 1988).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…In previous studies school maladjustment has been associated with child-to-parent violence (Ibabe et al, 2013; Ibabe, 2014), both variables could be indicators of psychological distress in adolescents. Taking into account that we will study a community sample, school failure could be a source of considerable family tension which might interfere with satisfactory relations between adolescents and parents (Hurrelmann et al, 1988).…”
Section: Introductionmentioning
confidence: 88%
“…Taking into account that we will study a community sample, school failure could be a source of considerable family tension which might interfere with satisfactory relations between adolescents and parents (Hurrelmann et al, 1988). In several previous studies low family cohesion has been found as an important risk factor of child-to-parent violent (e.g., Ibabe et al, 2013). …”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Este resultado podría sugerir que los adolescentes cometen actos violentos contra figuras de autoridad de su contexto cotidiano como expresión de rechazo, cuestionamiento y agresión (Emler y Reicher, 1995. Se sabe que aproximadamente el 35.3% de menores que agreden a sus padres utilizan la violencia en el contexto escolar, ya sea hacia iguales o hacia el profesorado (Ibabe, Jaureguizar y Bentler, 2013b), y que solamente en el 5% de los casos se hace referencia explícita a una clara implicación de la familia en el proceso escolar del menor (Romero et al, 2005).…”
Section: Discussionunclassified
“…En este orden de ideas, se ha observado que los jóvenes violentos en el hogar tienen relaciones familiares poco gratificantes, se identifican más con su grupo de pares que con sus progenitores y valoran a los amigos como los principales proveedores de apoyo emocional (Paulson et al, 1990). En esta línea, Ibabe et al (2007) señalan que el 65% de los jóvenes que maltratan a sus progenitores se relacionan con grupos disociales y violentos; asimismo, un 61.4% y un 65.2% presentan conductas violentas hacia iguales y conductas violentas hacia adultos, respectivamente, en especial contra otras figuras adultas de autoridad como los profesores (Ibabe et al, 2013b;Jaureguizar, Ibabe y Straus, 2013).…”
Section: Discussionunclassified